(untitled) (Latakia University Journal -Biological Sciences Series, 2019)
دلت النتائج على وجود تفاوت في قيم العجز المائي المناخي بين المناطق المدروسة ، وأكبر عجز مائي سنوي كان في حماه وبلغ -1673.3مم وأقلها في اللاذقية (-720.7مم ) وبينهما إدلب وحمص وخرابو بقيم بلغت على التوالي ( -1021.1 ، -1088.6،1184- مم ). لوحظ ازدياد الفروقات في الاحتياجات المائية للزيتون بين المناطق في مرحلة التطور و بلغت (231.9، 330.9، 312.9، 415.8مم) في كل من اللاذقية وإدلب وحمص وحماة على التوالي . أظهرت أشجار الفستق الحلبي مساراً سنوياً متشابهاً لاحتياجاتها المائية خلال موسم النمو في المناطق المدروسة وكانت قيم ETr متقاربة وأكبر قيمة سجلت في المرحلة الوسطية التي تمثل أكثر المراحل تطلباً للمياه، وبلغت في ادلب (122.5- 189.3)مم ،وفي حمص (121.5- 181.5)مم، و في حماة (138.2- 234.9)مم خلال نيسان وأيار على التوالي .أخيراً تشابه المسار السنوي للاحتياجات المائية للكرمة في المناطق الأربعة وسجلت حماة أعلى قيمة للاحتياجات المائية (295) مم في تموز من المرحلة الوسطية. Results refer that there are disparities in climatic water deficit values between the areas studied, and the biggest water deficit was in Hamah which reach -1673.3mm and the smallest value were in Lattakia-720.7 mm and between of them were Idleb, Homs and Kharabo with values reach (-1021.1,-1088.6, 1184mm) respectively. Increasing in the differences between olive’s water requirements between areas in development stage was observed, and the values became (231.9, 330.9, 312.9, 415.8mm)in Lattakia , Idleb, Homs and Hamah respectively. Pistachios water requirements has shown similar annual growth season trace in studied areas, ETr values were convergent and the biggest observing value was in mid stage which is the most water requirements stage, it was (122.5,189.3) mm in Idleb, in Homs(121.5-181.5) mm, and in Hamah (138.2 ,234.9)mm in April and May respectively. At last Grapes has similar annual growth season trace in the four areas and the highest value of water requirements was in Hamah (295) mm in July mid stage.